Strain-induced martensite decay in bearing steels under rolling contact fatigue: Modelling and atomic-scale characterisation. (15th October 2017) - Fu, Hanwei; Song, Wenwen; Galindo-Nava, Enrique I.; Rivera-Díaz-del-Castillo, Pedro E.J.
Abstract: Martensite decay in bearing steels manifested as dark etching regions (DERs) under rolling contact fatigue (RCF) is modelled. The proposed model is established based on a dislocation-assisted carbon migration mechanism. The proposed model is capable of predicting the progress of DER formation and the corresponding mechanical property evolution with increasing number of cycles, in good agreement with the experimental data reported throughout seventy years. The effects of RCF testing conditions on DER formation are studied and a useful tool, DER% maps, is developed for illustrating the temperature, contact pressure and number of cycles for DER occurrence. Moreover, an atom probe tomography study is carried out, revealing the nature of DER ferrite and obtaining strong evidence supporting the postulated DER formation mechanism. The successful application of the dislocation assisted carbon migration mechanism to DER formation provides a plausible explanation to the phenomenon of martensite decay under rolling contact fatigue. Graphical abstract: Image 1